Мотивы праздников церковного года в сочинениях митрополита киевского Илариона - Вилкул, Татъяна (Slavistica Vilnensis, 2010)
The author demonstrates that the composition of three works by Kievan Metropolitan Hilarion – Sermon on Law and Grace, Encomium to Vladimir, and Prayer – contains many citations from different Orthodox liturgical books, where the entire text is usually divided into portions to be read publicly in the church on particular feasts of the ecclesiastical year. The citations used by Hilarion are liturgically connected to a wide range of feasts, such as Easter, Epiphany, the Great Lent, Nativity of John the Baptist, Annunciation, Christmas, Nativity of the Theotokos, Ascension of Jesus, Pentecost, the Palm Week, the New Ecclesiastical Year, etc. It means that Hilarion’s works should not be regarded as specifically connected to a certain ecclesiastical feast, but rather as heortologically all-embracing texts.